DERL3 functions as a tumor suppressor in gastric cancer. (February 2020) - Li, Yongyuan; Liu, Hongjie; Chen, Hekai; Shao, Jianping; Su, Feng; Zhang, Shupeng; Cai, Xuejun; He, Xianghui
Graphical abstract: Highlights: A comprehensive analysis of STAD pathogenesis was conducted. High expression of DERL3 suppresses the invasion, migration, and proliferation of gastric cancer cells. DERL3 was screened and validated as a candidate diagnostic marker gene of STAD. DERL3 is a potential molecular target for the treatment of STAD. Abstract: Background: Gastric cancer is a common malignant tumor in the clinic with a high mortality rate, ranking the first among malignant tumors of the digestive system. Early gastric cancer exhibits no specific clinical symptoms and signs, and most of the patients were diagnosed as advanced gastric cancer. The prognosis is poor, and the 5-year overall survival rate is still lower than 30%, seriously threatening people's life and health. However, the pathogenesis of gastric cancer is still unclear. Methods: This study aimed to identify methylated differentially expressed genes in gastric cancer and to study the cellular functions and pathways that may be involved in its regulation, as well as the biological functions of key methylated differentially expressed genes. The gene expression data set and methylation data set of gastric cancer genes based on TCGA were analyzed to identify prognostic methylated genes. Results: This study showed that the methylation of the DERL3 promoter was correlated with the clinical analysis of tumors. Further studies were conducted on genes co-expressed with DERL3, whose functions and pathways to inhibit gastric cancer were adaptive immune response, T cell activation, immune response-regulating pathway, cell surface on molecules, and natural killer cell-mediated cytotoxicity. Finally, cell proliferation assay, cell scratch assay, and cell invasion assay confirmed that DERL3 as a tumor suppressor gene inhibited the malignant evolution of gastric cancer. Conclusions: The analysis of key methylated differentially expressed genes helped elucidate the epigenetic regulation mechanism in the development of gastric cancer. DERL3, as a methylation biomarker, has a predictive and prognostic value in the accurate diagnosis and treatment of gastric cancer and provides potential targets for the precision treatment of gastric cancer. Trial Registration: Not applicable.